2007
DOI: 10.1111/j.1463-1318.2007.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Is a morphologically intact anal sphincter necessary for success with sacral nerve modulation in patients with faecal incontinence?

Abstract: Objective Sacral nerve modulation (SNM) for the treatment of faecal incontinence was originally performed in patients with an intact anal sphincter or after repair of a sphincter defect. There is evidence that SNM can be performed in patients with faecal incontinence and an anal sphincter defect.Method Two groups of patients were analysed retrospectively to determine whether SNM is as effective in patients with faecal incontinence associated with an anal sphincter defect as in those with a morphologically inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 28 publications
2
82
2
3
Order By: Relevance
“…Several authors have reported good results in this type of patients with non-repaired external sphincter (23,24), and our experience confirms this. In our perspective two aspects remain to be defined along this line of work.…”
Section: Discussionsupporting
confidence: 79%
“…Several authors have reported good results in this type of patients with non-repaired external sphincter (23,24), and our experience confirms this. In our perspective two aspects remain to be defined along this line of work.…”
Section: Discussionsupporting
confidence: 79%
“…The PNE test is conducted over a period of 2-3 weeks. A positive test response is achieved for 70 %-90 % of patients (19)(20)(21)(22). In those who have an implanted stimulator, the effect is sustained in 70 %-90 % after 2-5 years (19,22,23).…”
Section: Anal Incontinencementioning
confidence: 99%
“…Patients with sphincter lesions covering up to one-third of the circumference can benefit from sacral nerve stimulation (20). However, sphincter lesions detected by ultrasound are a negative predictor of success (28), and large sphincter defects should probably first be treated by way of sphincter reconstruction.…”
Section: Anal Incontinencementioning
confidence: 99%
“…However, predictive factors that are necessary to reveal the efficacy of sacral neuromodulation prior to performing it remain to be unclear (33,34). The efficacy of sacral neuromodulation in partial sphincter injury has also been demonstrated (35)(36)(37). In patients with scleroderma having proctitis caused by radiation and reduced rectal compliance owing to inflammatory bowel syndrome and in patients with anterior resection or previous rectal prolapse colectomy, the efficacy of sacral neuromodulation is demonstrated only in few studies (38)(39)(40)(41)(42)(43).…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%